Le Brésil, puissance agricole : dynamiques récentes, projections, contradictions et fragilités (2006-2029) - Eduardo Paulon Girardi (Confins)
In this article we analyze the recent evolution (2006-2017) and projections (2019-2029) of the main products of Brazilian agriculture and livestock. The objective is to assess the regional dynamics of these products, its importance for the economy, for the internal market and for the trade balance. At the same time, we point out the contradictions and weaknesses of “Brazil's agricultural power”, built on the basis of a project to reprimarize the economy that constitutes an obstacle to the country's development and that intensifies the exploitation of natural resources.